Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga, Dan Brand Image Terhadap Keputusan Pembelian Kober Mie Setan Kota Kediri - Cempaka Dyah Pramita; Djunaedi; Sasi Utami; Enni Sustiyatik (Universitas Kadiri, 2024)
This study uses a quantitative approach, with data collected in the form of numbers and analyzed statistically, and meets scientific principles that are concrete, objective, measurable, rational, and systematic. The population of this study was all customers of Kober Mie Setan, Kediri City, totaling 150 respondents. The method used in sampling was the non-probability sampling method. The data collection methods used were documentation and questionnaires. The data were analyzed using validity tests, reliability tests, multiple linear regression assumptions with a confirmatory approach, and multiple linear regression analysis. The results of the study stated that: (1) Product quality has a positive and significant effect on buying decisions; (2) Service quality also has a positive and significant effect on buying decisions; (3) Price has no significant effect on buying decisions; and (4) Brand image has a positive and significant effect on buying decisions